Targeting Myelogenous Leukemia Stem Cells: Role of the Circulation - Liesveld, Jane (Frontiers in Oncology, 2012)
Unlike stem cells from solid tumors, the stem cells which initiate myelogenous leukemias arise in marrow, an organ with a unique circulation which allows ready access of leukemia cells, including leukemia stem cells, to the vasculature. This poses unique problems in the targeting of leukemic stem cells since these cells are found circulating in the majority of leukemia cases at diagnosis and are usually not detectable during remission states. Because most cases of leukemia relapse, it is suggested that leukemia stem cells remain quiescent in the marrow until they eventually proliferate and circulate again. This indicates that effective targeting of leukemia stem cells must occur not only in peripheral circulation but in the micro-circulation of the marrow. Targeting such interactions may overcome cell adhesion mediated treatment resistance, other multi-drug resistance mechanisms, and opportunities for clonal evolution in the marrow environment. Targeting selectins and integrins, signal transduction mediators, and chemokine/cytokine networks in the marrow micro-circulation may aid in abrogating leukemia initiating stem cells which contribute to disease relapse. Leukemia stem cells also possess surface antigen profiles and signal transduction activation profiles which may allow differential targeting as compared with normal hematopoietic stem cells.